Epigenetic maintenance of telomere identity in Drosophila: Buckle up for the sperm ride. - Dubruille, R.; Loppin, B. (Cell Cycle, 2011)
A critical function of telomeres is to prevent the ligation of chromosome ends by DNA repair enzymes. In most eukaryotes, telomeric DNA consists in large arrays of G-rich tandem repeats that are recognized by DNA binding capping proteins. Drosophila telomeres are unusual as they lack short tandem repeats. However, Drosophila capping proteins can bind chromosome extremities in a DNA sequence-independent manner. This epigenetic protection of fly telomeres has been essentially studied in somatic cells where capping proteins such as HOAP or HP1 are essential in preventing chromosome end-to-end fusions. HipHop and K81 are two recently identified paralogous capping proteins with complementary expression patterns. While HipHop is involved in telomere capping in somatic cells, K81 has specialized in the protection of telomeres in post-meiotic male germ cells. Remarkably, K81 is required for the stabilization of HOAP and HP1 at telomeres during the massive paternal chromatin remodeling that occurs during spermiogenesis and at fertilization. We thus propose that the maintenance of capping proteins at Drosophila sperm telomeres is crucial for the transmission of telomere identity to the diploid zygote. :